Factors Influencing Digital Technology Adoption in the South African Freight Transport Sector - Jaiswar, Sharday (University of the Witwatersrand, Johannesburg, 2024)
Considered essential to the functioning of the economy, the South African freight transport sector has experienced a decline in performance, negatively impacting South Africa’s global competitiveness and economic growth. Through benefit realisation, digital technology adoption has the potential to improve competitiveness and ultimately, enhance economic growth. With slow technology adoption rates observed in the South African freight transport sector, the research aimed to understand internal and external influencing factors of digital technology adoption, from an organisational context, within the sector. Furthermore, the influence of government support as a moderating factor was investigated. A combined theoretical framework was used for the study, consisting of the Technology Acceptance Model (TAM) and Technology-Organisation- Environment (TOE) framework. The quantitative research study utilised a survey to electronically collect data from freight transport organisations in South Africa, specifically in rail, port, pipeline and road industries. A stratified random sampling method was used, with sample size of 374. Key findings observed that perceived relative advantage, perceived ease of use of digital technologies and knowledge absorption capability were positively influencing internal factors, whereas competitive pressure and government support positively influenced the intention to adopt digital technologies from an external perspective. In addition, perceived ease of use of digital technologies mediated the relationship between perceived relative advantage and the intention to adopt digital technologies. Furthermore, government support as a moderator dampened the relationship between perceived ease of use of digital technologies and the intention to adopt digital technologies. The intention was to provide recommendations to enhance digital technology adoption for benefit realisation in the South African freight transport sector.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital technology; Digital technology adoption; South African Freight Transport Sector; Government support; Supply chain and logistics; TAM-TOE; UCTD; SDG-9: Industry, innovation and infrastructure